Ammonia Concentrations of Musts of Different Grape Cultivars and Vineyards in the Stellenbosch Area - Ougha, C. S.; Kriel, Abraham (South African Journal of Enology and Viticulture, 2017)
The ammonia concentrations of a large number of loads of grapes from different farms and of different cultivars were measured. Varietal differences were noted and statistical verifications made. Nine different cultivars were investigated. The average mean ammonia values for the cultivars varied from 54,9 to 148,l mg/(. Where enough loads from individual vineyards or growers were available, statistical differences were demonstrated. The conditions, treatment, and soil of the vines were shown to be reflected in the extremes by the juice ammonia concentrations. The use of these data is suggested as a means of assessing the vineyard's relative worth for winemaking purposes.